2007
DOI: 10.1111/j.1467-9957.2007.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

House Prices and Mortgage Credit: Empirical Evidence for Ireland*

Abstract: In Ireland, real property prices increased at an average of 12 per cent per annum from 1996 to 2002 with residential mortgage credit also increasing substantially. In this paper, the relationship between domestic bank credit and Irish house prices is examined empirically. Using a number of econometric approaches, we find evidence of a long-run mutually reinforcing relationship. The results are used to underpin a short-run system of the housing and credit sector. Simulations are then conducted to reveal the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 40 publications
10
99
1
1
Order By: Relevance
“…15 There is also a range of recent papers that confirm the empirical relevance of a financial accelerator effect in a housing context, see e.g. Fitzpatrick and McQuinn (2007); Berlinghieri (2010); Gimeno and Martinez-Carrascal (2010); Anundsen and Jansen (2013) for evidence from Ireland, the US, Spain and Norway, respectively.…”
Section: House Pricesmentioning
confidence: 98%
“…15 There is also a range of recent papers that confirm the empirical relevance of a financial accelerator effect in a housing context, see e.g. Fitzpatrick and McQuinn (2007); Berlinghieri (2010); Gimeno and Martinez-Carrascal (2010); Anundsen and Jansen (2013) for evidence from Ireland, the US, Spain and Norway, respectively.…”
Section: House Pricesmentioning
confidence: 98%
“…Empirical literature using this macroeconomic-type framework include both cross-country studies (Hofmann, 2001;Annett, 2005;Girouard et al, 2006;Sutton, 2002;Terrones and Otrok, 2004;Tsatsaronis and Zhu, 2004) and individual country studies (Fitzpatrick and McQuinn, 2004;Gerlach and Peng, 2005;and Gimeno and Martínez-Carrascal, 2006). The present paper borrows from these macro-type models.…”
Section: House Prices and Mortgage Financing: A Reviewmentioning
confidence: 99%
“…On the other hand, several cross-country evidence have indicated that the property have close relationship with mortgage lending (É gert & Mihaljek, 2007;Lacoviello & Minetti, 2008;Goodhart & Hofmann, 2008;Davis & Zhu, 2010). Capozza et al (2002), Gimeno and Martinez-Carrascal (2006);and Fitzpatrick and McQuinn (2007) investigate the case of USA, Spain and Irland respectively and reach the same conclusion. Liang and Cao (2007) find a unidirectional causality from bank lending, interest rate and income to property prices in China.…”
Section: Literature Reviewmentioning
confidence: 52%